2016
DOI: 10.1111/apm.12625
|View full text |Cite
|
Sign up to set email alerts
|

HE4 as a predictor of adjuvant chemotherapy resistance and survival in patients with epithelial ovarian cancer

Abstract: The aim of this study was to investigate the value of serum human epididymis protein 4 (HE4) and HE4 tissue protein expression to predict tumor resistance to adjuvant chemotherapy, progression-free survival (PFS), and overall survival in patients with epithelial ovarian cancer (EOC). Consecutive inclusion of 198 patients diagnosed with EOC was conducted. Blood samples were collected prior to surgery and tissue samples during surgery. Patient data were registered prospectively in the Danish Gynecologic Cancer D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…In these studies, the preoperative HE4 median values were about 400 pmol/L. Most of the studies that have used a standard HE4 cut-off of 70 pmol/L, as usually proposed for cancer detection, or a continuous log-transformed HE4 variable failed to detect an association between presurgical HE4 levels and survival [2528]. In the first case, we could easily anticipate that the optimal HE4 threshold for EOC prediction would be higher than the threshold for EOC detection.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, the preoperative HE4 median values were about 400 pmol/L. Most of the studies that have used a standard HE4 cut-off of 70 pmol/L, as usually proposed for cancer detection, or a continuous log-transformed HE4 variable failed to detect an association between presurgical HE4 levels and survival [2528]. In the first case, we could easily anticipate that the optimal HE4 threshold for EOC prediction would be higher than the threshold for EOC detection.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that HE4 is associated with chemotherapy resistance in tumor cells [23][24][25] ; HE4 could induce drug resistance in ovarian cancer cells by activating the AKT and ERK pathways and was associated with poor prognosis in ovarian cancer patients 24 ; HE4 could also interact with EGFR, IGFR, and, the transcription factor, HIF1α, thereby promoting ovarian cancer cell invasiveness and drug resistance and, consequently, worsening the prognosis of ovarian patients 26 ; the over expression of HE4 was also noted to promote cisplatin-and paclitaxel-resistance in ovarian cancer, where the down-regulation of HE4 reversed resistance to many drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, their AUCs were not greater than 0.8, indicating that these findings could not be directly applied to clinical practice. Current studies that have reported that HE4 and mesothelin could be used as ovarian tumor markers [28][29][30][31]. Additionally, one study showed that HE4 protein promoted the proliferation of ovarian cancer cells and resistance to carboplatin in vitro, suggesting the value of HE4 in predicting the growth potential of epithelial ovarian cancer tumors and platinum resistance [32].…”
Section: Discussionmentioning
confidence: 99%